2018
DOI: 10.1038/pr.2017.304
|View full text |Cite
|
Sign up to set email alerts
|

B2 adrenergic receptor gene polymorphism effect on childhood asthma severity and response to treatment

Abstract: BackgroundAlterations of B2 adrenergic receptor (βAR) can modulate the severity of asthma and the response to treatment. Therefore, we aimed to evaluate βAR gene polymorphism at codons 16 and 27 and their effect on asthma severity and response to treatment in asthmatic children.MethodsCase-control study was conducted on 156 children; 104 of them had bronchial asthma and 52 were healthy children (control group). Subjects of the study underwent history taking, clinical examination, pulmonary function tests, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Between 2018 and 2019, the pharmacogenetic studies conducted in pediatric asthma have been mainly focused on therapeutic response to ICS and SABA albeit some of them have studied simultaneously the response to ICS and LABA/ LTRA. Altogether, eleven candidate-gene studies, [24][25][26][27][28][55][56][57][58][59] a meta-analysis of a candidate gene, 60 and six pharmacogenomic studies (one of them in adults but including replication in children) have been performed. 32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Between 2018 and 2019, the pharmacogenetic studies conducted in pediatric asthma have been mainly focused on therapeutic response to ICS and SABA albeit some of them have studied simultaneously the response to ICS and LABA/ LTRA. Altogether, eleven candidate-gene studies, [24][25][26][27][28][55][56][57][58][59] a meta-analysis of a candidate gene, 60 and six pharmacogenomic studies (one of them in adults but including replication in children) have been performed. 32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA).…”
Section: Discussionmentioning
confidence: 99%
“…16,18,23 It encodes the β 2 adrenergic receptor, which is implicated in the bronchodilation process and is the biological target of β 2 adrenergic agonists. 19 In fact, in the reviewed period four candidate-gene studies have assessed the effect of the SNPs rs1042713 (arginine to glycine [Arg16Gly]) and rs1042714 (glutamic acid to glutamine [Glu27Gln]) on changes in lung function after SABA administration in European 24,25 and Egyptian 26,27 populations (Table 1). However, the results were not entirely consistent across studies.…”
Section: Candidate-gene Studies Of Saba Responsementioning
confidence: 99%
See 3 more Smart Citations